The Political Cultures of Forwarding on Chinese Social Media: Lessons From Hong Kong Chief Executive Election. (April 2019) - Zhao, Yupei; Lin, Zhongxuan
This research draws on De Maeyer's three-level mixed methodological framework and examines how, and to what extent social media users interpret their ideological use of "forwarding" for political participation with explicit and implicit political purposes on social media. It does so by examining the case of the 2017 Hong Kong Chief Executive election. Quantitative content analysis ( N = 22, 172) and semi-structured interviews ( N = 150) are combined to examine the rise of a new and distinctly multifactorial political discourse—"forwarding"—as used by both Hong Kong and Mainland China users. In doing so, an attempt is made to explore the premises and consequences of this implicit discourse. This research finds that the interpretation of forwarding is convoluted, but it can be seen to accelerate the much-desired prospect of Chinese social media's ability, on one hand, to amplify citizens' political deliberative participation and extend their political influence and, on the other hand, to be representative of the political extremes and to refer to critiques of specific political realities. Thus, this article discusses four dimensions of the political culture of forwarding that perform the function of Chinese-style surrogate democracy: These dimensions are particularly attributable to the statuses and geographical backgrounds of the users of the social media website Weibo.